Pemikiran Akhlak Sultan Alauddin Suleiman Shah: Tinjauan Terhadap Karya Nasihat Pemeliharaan Guru – Melatih Kelakuan Perjalanan Adab Kanak-kanak: Sultan Alauddin Suleiman Shah's Akhlak Thought: A Review of ‘Nasihat Pemeliharaan Guru – Melatih Kelakuan Perjalanan Adab Kanak-Kanak’ - Muhammad Hifzurdin Hussin,; Abdul Hamid, Faisal@Ahmad Faisal (Journal Al-Muqaddimah, 2024)
Sultan Alauddin Suleiman Shah ibni Almarhum Raja Muda Musa ruled Selangor Darul Ehsan from 1898 till his death in 1938. His authority and significant contributions, particularly in the development of Islamic knowledge and education in Selangor, have been recorded in various writings by English colonial administrators and historians. Selangor attained significant educational achievements under his reign as a result of his commitment to human capital development, notably through the advancement of faith and morality. Individuals who establish Islamic faith and tauhid must always cultivate strong morals and ethics. This is because good character enables people to practice Islamic ideals in their daily lives, such as honesty, trustworthiness, compassion, and justice, all of which are vital to Islamic teachings. This article will examine the work “Nasihat Pemeliharaan Guru – Melatih Kelakuan Perjalanan Adab Kanak-Kanak " in terms of both writing methods and substance. The project will use data collecting and literature review methodologies.